Assessment of the Effectiveness of Global Climate Policies Using Coupled Bottom-up and Top-down Models - Maryse Labriet; Laurent Drouet; Marc Vielle; Richard Loulou; Amit Kanudia; Alain Haurie (Fondazione Eni Enrico Mattei (FEEM), 2015)
In order to assess climate mitigation agreements, we propose an iterative procedure linking TIAM-WORLD, a global technology-rich optimization model, and GEMINI-E3, a global general equilibrium model. The coupling methodology combines the precise representation of energy and technology choices with a coherent representation of the macro-economic impacts, especially in terms of trade effects of climate policies on energy-intensive products. In climate mitigation scenarios, drastic technology breakthroughs are required as soon as possible, especially in large emitting countries, and in all sectors of the economy. Energy-intensive industries tend to be delocalized in regions where low-carbon production is feasible and cheap, or in regions without emission cap. However, emission leakage remains small, mainly due to global lower oil demand, and energy exporting countries are extremely penalized given lower energy exports. Emission reduction at least in the power sector and in energy-intensive industries of developing countries must be considered to reach the 2°C target.
Keywords: Q5; Q54; Q58; 330; Climate Policies; Energy; Techno-economic modelling; Macro-economic Modelling; World